Automation Storage System Based On SCADA Using PLC CP1H and CP1L - Gun Gun Maulana; Ridwan Mada; Regim Ramaya Purba (Universitas Syiah Kuala, 2022)
The warehousing system is a means of supporting production activities and industrial operations that function to store goods to be distributed, which are still using a manual system and must adapt to technological developments. The problem that often arises in the warehousing system that is still done manually is that the flow of goods into the warehouse is not well organized, and this makes it difficult when the goods are about to be removed, so it requires a longer search time. Previous research has shown actual data on storage racks that use Arduino Mega as a controller and VB as an interface, but there is no actual data on the state of the lifter or the selection of lifter movement speed modes to facilitate operators in monitoring and operating goods storage. Control systems with industry standards greatly affect the effectiveness and optimization of the production process. Based on these problems, this research aims to simplify the managerial and monitoring process in the warehouse with a prototype of automatic multilevel storage using PLC CP1H and CP1L as system control and Wonderware Intouch as an interface with the SCADA system. The prototype has 12 cells, and each cell can accommodate 2 boxes; each cell is distinguished by the height and color of the box. In testing this research, the SCADA system can work optimally. The interface is capable of displaying the actual data of the rack with a success rate of 100%, the hardware error rate is less than 1%, and the interface can display the actual data on the state of the lifter.